Information and organization a new perspective on the theory of the firm - Casson, Mark, 1945-; Oxford eBooks (New York ; Oxford : Oxford University Press, 1997)
Information and Organization models the economy in terms of the flow of information rather than material goods. Instead of the adverserial exploitation of information gaps, it stresses the creative use of information in decision making.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Microeconomics; Industrial organization (Economic theory); Entrepreneurship; Decision making; Information resources management; Industrial management; Electronic books